COMPETITIVENESS AND INNOVATION: THE ROLE OF SMES IN INCREASING COMPETITIVENESS - Vajda, Andrea (Acta Carolus Robertus, 2020)
Competitiveness and innovation are key concepts in economics, but their definition is difficult and in many ways controversial. Competitiveness has been analysed by many authors who agree that a universally accepted definition is not yet available. Competition has grown global by nowadays. Companies may have sustained competitive advantage through capability to innovate, knowledge creation and knowledge-transfer. An important part of this dissertation is the analysis of the changing trends and the competitiveness of Hungary on the basis of the 12 pillars of WEF. The tendency between 2007 and 2017 is deteriorating in general; positive changes can only be detected in recent years. The development of human resources is essential for success. Hungary can only succeed with a well-established knowledge-based society.